IMPROVING GRADE 1 STUDENTS, UNDERSTANDING OF ADDING AND SUBTRACTING NUMBERS USING STARWS AND CONNTING BOARDS AT SDI ENDE 14 - Muhamad Dahril; Adi Neneng Abdullah (Media Inovasi Pendidikan dan Publikasi, 2024)
The aim of this research is to increase students, understanding of addition band subtraction of numbers using straws and counting boards in grade 1 elementary school students. The method used is ptk which is carried out at sdi ende 14. As for the results obntained, students fell enthusiastic about participating in the lerning proces, they can experience direct addition and subtraction activities. The sujects of this research were 20 student in clas 1 at ende 14, the data was taken using test , observation and documentation technicues, students also had knowledge about the magnitude of numbers , so they could answer the amount that was subtracted and the amount thas was added. They result of the search showed that after using starws and conting boards, learning outcomes in mathematics learning were 25% in cycle 1 to 100% in cycle 2. Mathematics learning activities in cycle one were in the quite active category and increased to the very active category in cycle 2 thus, straw media and counting boards can improve the quality of learning in grade 1 to 14.